Hypovitaminosis D upscales B-cell immunoreactivity in multiple sclerosis - Haas, Jürgen; Schwarz, Alexander; Korporal-Kuhnke, Mirjam; Faller, Simon; Jarius, Sven; Wildemann, Brigitte (Journal of neuroimmunology, 2016)
Background - While vitamin D is increasingly recognized as a potential immune regulator of MS disease activity, its impact on B lymphocytes, however, remains ill-defined. - Methods - We assessed the impact of vitamin D on B-cell proliferation and cytokine secretion ex vivo and screened for effects of hypovitaminosis D and vitamin D supplementation on the compartmentalized distribution of B-cell subtypes in peripheral blood and cerebrospinal fluid (CSF) from patients with relapsing remitting MS (n=95) and various neurologic and healthy controls (n=57). - Results - B cells from MS patients with 25(OH)D serum levels <20ng/ml, displayed enhanced immunoreactivity ex vivo as a consequence of more vigorous responses of CD27+ memory phenotypes. Immune responses decreased when B cells from either source were co-cultured in the presence of vitamin D or when retesting B cells from MS patients after prolonged supplementation with vitamin D. Hypovitaminosis D was detectable in the serum of 40/95 MS patients, correlated with decreased vitamin D concentrations in CSF and with higher disease activity, and was paralleled by intrathecal accumulation of CD27+ B-cell subtypes and plasma cells. - Conclusion - B-cell immunoreactivity is attenuated by vitamin D. Our finding that vitamin D deficiency affects the intrathecal compartment and coincides with increased frequencies of effector B-cell subtypes in the CSF suggests that hypovitaminosis D might contribute to augmenting disease activity in the target organ and supports a potential benefit of vitamin D supplementation in MS.
Gesehen am 11.09.2019